ESTABLISHING A MARKET FOR HUMAN ORGANS* IN SOUTH AFRICA PART 1: A PROPOSAL** - Magda Slabbert; Hennie Oosthuizen (Obiter, 2022)
In the current system of organ procurement in South Africa, demand for transplantable organs outstrips supply by far. A change in legislation governing donation of organs is desperately needed as too many patients die unnecessarily waiting for an organ. A possible solution is to reward the donor financially. Authors in other countries have also expressed the need for changes in their countries’ legislation in order to legalise the sale of human organs for transplant in an effort to save more lives. The proposed way of regulating the trade in organs is through “futures contracts”. In order to propose a market for human organs in South Africa, it is necessary to take note of these proposals. A problem highlighted is the question whether property rights in human organs exist. Although not legislated in South Africa, it will be shown that there are property rights in human body parts. Finally, a contract of sale for selling kidneys from living donors and a futures contract for the sale of transplantable organs from a deceased donor will be proposed after analysing arguments against the commercialisation of human organs. In Part 2 the shortcomings in South African legislation, specifically regarding organ transplants will be discussed. Solutions will be suggested in accordance with the four pillars of bioethics.